Analisis Metode Dan Gaya Mengajar Guru Sebagai Sumber Gangguan Disiplin Kelas Terhadap Kondisi Peserta Didik - Zulli Nurrita; Shofwatul Qolbiyah; Muhammad Qoidul Ghurril Muhajjalin; Khoridatul Azizah (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This article aims to analyze the sources of classroom disciplinary disturbances and their impact on student performance. This research examines internal factors such as learning motivation, self-control, and emotional state, as well as external factors including the family environment, social interactions, and school culture, which contribute to disciplinary violations. Furthermore, the roles of schools and families are analyzed as two primary environments in shaping disciplinary behavior through coaching, supervision, and role modeling. The results of the study indicate that disciplinary violations have a significant impact on the learning process, including reducing concentration, hindering learning effectiveness, and affecting academic achievement. Furthermore, disciplinary disturbances are also closely related to students' psychological and social conditions, such as a low sense of responsibility and difficulties in adjustment. Therefore, ongoing synergy between schools and families is needed to create a conducive learning environment and support the optimal development of students' disciplinary character.